Assessment of Incidence and Prevalence of Prostate Cancer in Middle Aged Male Patients of Western Nepal Using Prostate-specific Antigen and Digital Rectal Examination that Underwent Prostate Biopsy: Assessment of Incidence and Prevalence of Prostate Cancer in Middle Aged Male Patients of Western Nepal Using Prostate-specific Antigen and Digital Rectal Examination that Underwent Prostate Biopsy - Sharma, Suman (International Journal of Pharmaceutical & Biological Archive, 2020)
This study was conducted to evaluate the incidence of prostate cancer (PCa) in male patients with increased prostate-specific antigen (PSA), and normal or abnormal digital rectal examination (DRE) that underwent a prostate biopsy. From March 2018 to November 2018, a total of 98 consecutive males suspected of having PCa due to increased PSA levels underwent transrectal ultrasonography (TRUS)-guided sextant biopsy of the prostate. The total PSA (tPSA), demographic data, the incidence of PCa, benign prostate hyperplasia (BPH), and prostatitis were assessed. The patients were divided into two groups according to their PSA values (Group A serum tPSA level, 4–10 ng/mL; and Group B serum tPSA level, 10.1–20.0 ng/mL). Of the 98 biopsied cases, 56% had PCa, 23% had BPH, and 21% had prostatitis. The mean PSA and the age of the carcinoma group were significantly higher than those of the benign group (P < 0.01). The biopsy results were grouped as PCa, BPH, and prostatitis. The incidence of PCa for Group A and Group B cases was 51% and 65%, respectively. In the case of PCa, BPH, and prostatitis, the mean PSAs were 10.02 ng/mL, 8.76 ng/mL, and 8.41 ng/mL, respectively (P < 0.40). In conclusion, TRUS-guided prostate biopsy and interpretation by a skilled team are highly recommended for early detection of PCa or its ruling-out. Due to the very high incidence of PCa in the patients with PSA >10 ng/mL, TRUS-guided biopsy is indicated, whatever the findings on DRE and/or LUTS, since the PCa detection rate is high.